2007
DOI: 10.1016/j.bbrc.2007.06.143
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated oxysterol, 25HC3S, is a potent regulator of lipid metabolism in human hepatocytes

Abstract: Recently, a novel oxysterol, 5-cholesten-3β, 25-diol 3-sulfate (25HC3S) was identified in primary rat hepatocytes following overexpression of the cholesterol transport protein, StarD1. This oxysterol was also detected in human liver nuclei. In the present study, 25HC3S was chemically synthesized. Addition of 25HC3S (6 μM) to human hepatocytes markedly inhibited cholesterol biosynthesis. Quantitative RT-PCR and Western blot analysis showed that 25HC3S strongly decreased HMG-CoA reductase mRNA and protein levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 40 publications
4
57
0
Order By: Relevance
“…6,48) The overexpression of FAS has promoted fatty acid synthesis and lipogenesis. [48][49][50] A previous study has also clarified that feeding ethanol in micropigs increased the expression of such lipogenic enzymes as SREBP-1c, FAS, acetyl-CoA carboxylase and stearoyl-CoA desaturase.…”
Section: Discussionmentioning
confidence: 97%
“…6,48) The overexpression of FAS has promoted fatty acid synthesis and lipogenesis. [48][49][50] A previous study has also clarified that feeding ethanol in micropigs increased the expression of such lipogenic enzymes as SREBP-1c, FAS, acetyl-CoA carboxylase and stearoyl-CoA desaturase.…”
Section: Discussionmentioning
confidence: 97%
“…Hepatic StAR expression was increased 7-and 15-fold in steatosis and NASH patients, respectively 11 , thereby enhancing mitochondrial free cholesterol accumulation and toxicity Heterozygous NPC1/2 deficiency leads to fatty liver, obesity and metabolic syndrome 82 NPC1 gene is linked to to early-onset and morbid adult obesity in Europeans 83 ORP8 ↓ hepatic cholesterol and triglyceride accumulation by inhibiting activation of SREBP-2 and SREBP-1c ORP8 ↑ hepatic insulin sensitivity through an AKTmediated mechanism 86,87 Cholesterol absorption and secretion [39][40][41] 25OHC3S had opposite effects than 25OHC on lipid metabolism and inflammation and improved NAFLD in cellular and mouse models( [39][40][41] Enhancement of on of SULT2B1b activity may counteract effects of toxic oxysterols …”
Section: Biological Effectmentioning
confidence: 99%
“…This sulfated oxysterol was believed to be initially synthesized by CYP27A1 in mitochondria (15). It has been reported that the addition of 25HC3S to primary human hepatocytes decreases cholesterol and fatty acid biosynthesis by blocking the activation of sterol-regulatory element binding protein-1c and inhibiting its expression (16). These results suggest that 25HC3S plays an important role in the maintenance of intracellular cholesterol and lipid homeostasis.…”
mentioning
confidence: 99%
“…However, to date, little is known about the role of SULTs in cholesterol metabolism in the liver. It is likely that SULT2B1b is involved in oxysterol sulfation, which plays an important role in lipid metabolism in liver (16).…”
mentioning
confidence: 99%